The effect of the shape of a clip on the magnetic field during magnetic resonance imaging examinations - Samir Delibegović; Mirza Batalović; Mirela Delibegović; Tarik Bujaković (Medicinski glasnik, 2022)
Aim: Plastic clips are a diamagnetic material and produce fewer artefacts in the MR field than titanium clips, which are standard in neurosurgery. However, alongside their physical properties, the shape of the clips, and their very geometry subtlety affects their behaviour in the magnetic field. Therefore, we performed a simulation in order to establish which clips cause less disturbance in the magnetic field from the point of view of the geometry of the body. Methods: The simulation tool used for the research was the software package COMSOL Mph version 4.3. Since it was a question of magnetics, the models were prepared in the AC/DC module within the option Magnetic Fields, No Currents (mfnc). Within this module we were able to analyse electro-magnetic fields for a specific geometrical structure, using the Finite Element Method: in order to resolve the two-dimensional electromagnetic problems. Results: The value of the magnetic field with titanium clips with their specific geometric reference lines reached the value of c. (A/m). The simpler geometry of the plastic clips resulted in a less intensive magnetic field, amounting to c. (A/m), which is an entire order of magnitude less than the field with the titanium clips. Conclusion: The simpler geometry of the plastic clips and the type of material from which they are made causes less disturbance to the magnetic field, which was precisely confirmed with the simulation model. The use of plastic clips in neurosurgery and neuroradiology will facilitate the interpretation of MR images.
Keywords: geometry of an object; magnetic field; plastic clip; titanium clip